Rat angiotensin-converting enzyme : tissue specific expression during pharmacological inhibition - Brice, Edmund Andrew William (Division of Medical Biochemistry and Structural Biology, 2018)
The renin-angiotensin system plays a central role in the maintenance of blood pressure. Angiotensin II, the main effector of this system, results from the action of angiotensin-converting enzyme (ACE) on angiotensin I. Angiotensin II, maintains vasomotor tone via its vasoconstrictor action, and also increases salt and water retention by stimulating the release of aldosterone. ACE inhibitors, such as captopril, enalapril and lisinopril, are highly effective in the treatment of hypertension and congestive cardiac failure. Previous studies have suggested that angiotensin converting enzyme (ACE) production may be enhanced during pharmacological inhibition of the enzyme. Little is known, however about the mechanism of this induction. After demonstrating increases in circulating ACE protein in cardiac failure patients receiving the ACE inhibitor captopril, a rat model was used to study this effect. A sensitive enzyme linked immunosorbent assay for rat ACE was developed and a partial cDNA for rat ACE cloned to enable examination of ACE mRNA and protein expression during enzyme inhibition with enalapril. Rat lung ACE mRNA increased by 156% (p<0.05) and ACE protein doubled within 3 hours of administering a single dose of enalapril. Testicular ACE mRNA also increased by 300% (p<0.05) within 2 hours and returned to pretreatment levels by 6 hours. The angiotensin II antagonist saralasin similarly caused a significant (p<0.0001) 800% enhancement of mRNA expression. Aldosterone pretreatment of rats prior to enalapril administration was found to abolish this mRNA induction. These findings indicate that increased ACE expression during inhibition results from reduced levels of angiotensin II with consequent reduced stimulation of the angiotensin 11 receptor and its effects, such as aldosterone release. This suggests that ACE levels are regulated by a negative feedback loop involving the distal components of the renin-angiotensin system, namely angiotensin II and aldosterone. In situ hybridisation and immunohistochemical techniques were employed to localise the site of this inductive response in rat tissue sections. It was found that lung macrophages were markedly induced to produce ACE, as was ACE in seminiferous tubules. ACE induction was also noted in the expected sites of renal tubular epithelium and glomerular tissue. Interestingly, ACE expression was also enhanced in cardiac valves. In these studies it has been conclusively demonstrated that new ACE expression is induced by enzyme inhibitor therapy. A variety of techniques have been developed that will allow futher study of ACE in rat tissues.